Nutritional profile and pharmacological aspect of Houttuynia cordata Thunb. and their therapeutic applications - Srimay Pradhan; Swati Rituparna; Haripriya Dehury; Monalisa Dhall; Yengkhom Disco Singh (Elsevier, 2023)
Introduction: Houttuynia cordata Thunb, a perennial plant indigenous to East Asia and the northeastern region of India, belongs to the Saururaceae family. Thriving in shaded environments, this plant is commonly harvested from moist habitats and local markets for research purposes, while also serving as a valuable resource in various sectors, including food, medicine, and commerce. This study aims to comprehensively explore the plant's morphology, distribution, traditional uses, nutritional composition, pharmacological characteristics, prominent bioactive compounds, therapeutic applications, and potential future prospects. Methods: The study involves an extensive review of existing literature and research findings concerning H. cordata. Information regarding its botanical characteristics, geographical distribution, and historical utilization is collected from diverse sources. Results: The research findings reveal that H. cordata possesses a wide range of therapeutic applications, including antibacterial, antifungal, antimicrobial, antiviral, anticancer, antimutagenic, anti-obesity, anti-corona, antioxidative, and anti-inflammatory activities. Notably, the significant bioactive compounds extracted from this plant, such as quercetin, quercitrin, and isoquercitrin, exhibit diverse and promising applications. Discussion: The study underscores the importance of H. cordata as a valuable natural resource with a rich history of traditional use and a burgeoning recognition for its diverse applications. Its therapeutic properties, ranging from combating infections to addressing chronic diseases like cancer, highlight its significance in modern medicine. The presence of major bioactive compounds, particularly flavonoids, further accentuates its potential in pharmaceutical and nutritional industries. Looking ahead, future research should prioritize in vitro and in vivo clinical experiments to advance our understanding of this plant's mechanisms of action and enhance its contribution to human healthcare.